Hubungan Kebiasaan Merokok dengan Tekanan Darah pada Pria Dewasa di Desa Kraton Kota Bangkalan - Khuzaimah, Fitkiyah Nurul; Mutazam, Ali; Irawan, Dimas Sondang (Jurnal Kesehatan, 2024)
Smoking is an activity that is often found among the public. The highest prevalence of smoking rates occurred at the age of 45-54 years, with a percentage of 28.5%. Smoking habits can have negative impacts on health, especially on blood pressure. The purpose of this study was to determine the relationship between smoking habits and blood pressure in adult men. This study used an analytic observation method with a cross-sectional design. The study population was adult men in the village of Kraton, and there were as many as 148 people. The sampling technique was purposive sampling, that met the inclusion criteria, so a sample of 91 people was obtained. Data collection was done using questionnaires and by checking the blood pressure. The data was then analyzed using the chi-square test. The bivariate analysis result shows that there is a significant relationship between smoking habits and blood pressure with a p-value of 0.002 <0.05. This study concluded that there is a relationship between smoking habits and blood pressure in adult men.